Insights from two decades of the Student Conference on Conservation Science. (March 2020) - Geldmann, Jonas; Alves-Pinto, Helena; Amano, Tatsuya; Bartlett, Harriet; Christie, Alec P.; Collas, Lydia; Cooke, Sophia C.; Correa, Roberto; Cripps, Imogen; Doherty, Anya; Finch, Tom; Garnett, Emma E.; et al.
Abstract: Conservation science is a crisis-oriented discipline focused on reducing human impacts on nature. To explore how the field has changed over the past two decades, we analyzed 3245 applications for oral presentations submitted to the Student Conference on Conservation Science (SCCS) in Cambridge, UK. SCCS has been running every year since 2000, aims for global representation by providing bursaries to early-career conservationists from lower-income countries, and has never had a thematic focus, beyond conservation in the broadest sense. We found that the majority of projects submitted to SCCS were based on primary biological data collected from local scale field studies in the tropics, contrary to established literature which highlights gaps in tropical research. Our results showed a small increase over time in submissions framed around how nature benefits people as well as a small increase in submissions integrating social science. Our findings suggest that students and early-career conservationists could provide pathways to increase availability of data from the tropics and address well-known biases in the published literature towards wealthier countries. We hope this research will motivate efforts to support student projects, ensuring data and results are published and data made publicly available. Highlights: Results from student submissions show different patterns to published literature. The majority of submissions were based on primary biological data collection. Fieldwork was primarily conducted in the tropics. There was a small increase over time in submissions on nature benefits people. There was a small increase over time in submissions integrating social science.